2016
DOI: 10.48208/headachemed.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Medication overuse headache and its specific clinical markers

Abstract: Introduction: Clinical markers of medication overuse headache (MOH) are based on headache classification developed by the International Headache Society (IHS). This classification include only two criteria: 1) frequency of headache must be 15 or more days per month for at least three or more months; 2) the number of days of overuse medication must be either 10 or 15 days per month depending on the type of medication. However, patients often present with associated clinical markers that are overlooked by most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Besides, it was observed that the scale compared with a structured clinical interview, for a cutoff point of 20/40, showed a sensitivity of 95.5%, a specificity of 70.3%, a positive predictive value of 38.9%, a value negative predictive of 98.7%, positive probability ratio of 3.2, negative probability ratio of 0.07, Cohen's kappa of 0.42, and area under the curve of 0.90; similar to the original 20‐item version 10 . Therefore, the Brief Spanish Zung Self‐Rating Depression Scale has been used to quantify depressive symptoms in other studies in Latin America 11‐15 …”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was observed that the scale compared with a structured clinical interview, for a cutoff point of 20/40, showed a sensitivity of 95.5%, a specificity of 70.3%, a positive predictive value of 38.9%, a value negative predictive of 98.7%, positive probability ratio of 3.2, negative probability ratio of 0.07, Cohen's kappa of 0.42, and area under the curve of 0.90; similar to the original 20‐item version 10 . Therefore, the Brief Spanish Zung Self‐Rating Depression Scale has been used to quantify depressive symptoms in other studies in Latin America 11‐15 …”
Section: Introductionmentioning
confidence: 99%